Pyocolpos in a 4 year old: a rare scenario - Agarwal, Neha; Singh, Saroj; Dayal, Rajeshwar; Pathak, Anu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Pyocolpos is cystic dilatation of vagina due to accumulation of pus resulting from genital tract obstruction. Hydrocolpos or pyocolpos are usually encountered either in the neonatal period due to stimulation from maternal hormones or at menarche. Their occurrence beyond infancy and before puberty is rare. We report this rare case of pyocolpos in a 4 year old child.